Impact of functional disability on lifestyle for patients with arthritis - ali, mohammed (Iraqi National Journal of Nursing Specialties, 2005)
A descriptive study, which was using an assessment approach, was conducted for thedetermination of the impact of rheumatoid arthritis and osteoarthritis patient’s functional disabilityupon their life style. The study was carried out at the Rheumatology and outpatients clinics of ALKaramaTeaching Hospital, Baghdad Teaching Hospital AL-Kindey Teaching Hospital and Specializedsurgeries Teaching Hospital for the period of October 15th 2003 through May 13th 2004 in BaghdadCity. A purposive (non-probability) sample of (245) arthritis patients which was comprised (111)rheumatoid arthritis patients and (134) osteoarthritis patients, was selected out of the early statedsettings. The questionnaire was comprised of two main parts. Part one dealing withsociodemographical data like (age, sex, marital status, education level) and part two was includinglifestyle domains of physical, occupation, social, environmental emotional and spiritual.The findings of the study presented that these patients functional disability had great impactupon their lifestyle with regard to their daily living activities, such as dressing, cleaning, walking andworking, as well as the domains of family interaction, environmental interaction and emotionaldisorders. The study recommended that well designed and structured health education program can bepresented to these patients with respect to preventive, curative and rehabilitative issues by whichcomplications can be reduced and health status can be promoted and maintained through the exerciseprogram, drugs montoring and follow-up and patients education about the disease and drugs sideeffects.